Levels of salivary cysteine in periodontitis patients with and without hopeless teeth: diagnostic validity of the assay - Tassi, Carmelo; Lotito, Massimo (Journal of Osseointegration, 2010)
in previous studies. The aim of our study was to assess the diagnostic accuracy of salivary assays for the determination of cysteine levels in periodontal patients. Materials and Methods Cysteine concentration was measured, by HPLC, in saliva samples of 15 patients with healthy periodontium (negative controls), and 35 periodontitis patients (tests) 18 with and 17 without hopeless teeth. The cysteine values were analyzed by Receiver Operating Characteristic (ROC) curve analysis in order to assess the diagnostic accuracy of salivary cysteine determination. Results and conclusion Salivary levels of cysteine were significantly higher (P<0.01) in periodontitis patients than in controls. Levels were significantly higher (P<0.01) in periodontitis patients with hopeless teeth than in those without. The evaluation of salivary cysteine concentration by ROC curve analysis demonstrated diagnostic accuracy as a biochemical marker to identify periodontitis affected patients and distinguishes between patients with or without hopeless teeth.